PENGARUH KECANDUAN BERMAIN GAME ONLINE TERHADAP PRESTASI BELAJAR SISWA DI SMK Negeri 6 BATANG HARI - Tri Wahyu Ningsih; Muhammad Ferdiansyah; Desy Susanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of science and technology has influenced students’ learning behaviors and lifestyles, including the increasing tendency toward online game addiction, which may affect academic achievement. This study aimed to examine the effect of online game addiction on students’ academic achievement at SMK Negeri 6 Batang Hari. The research employed a quantitative approach using an ex post facto design. The population consisted of 150 students, with 109 students selected through purposive sampling, namely those who played online games for 1–10 hours per day. Data were collected using questionnaires and supported by observation, then analyzed using descriptive statistics and simple linear regression analysis. The results showed that students’ level of online game addiction was categorized as high, with a mean score of 74.99. Regression analysis revealed a significant negative effect of online game addiction on academic achievement, with a regression coefficient of −0.480 and a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) was 0.397, indicating that online game addiction contributed 39.7% to variations in academic achievement, while the remaining 60.3% was influenced by other factors such as motivation, family environment, learning interest, and psychological conditions. These findings indicate that a high level of online game addiction can negatively affect students’ academic achievement if not properly managed.